Investigating micrometeorological differences between saline steppe, forest-steppe and forest environments in northern Serbia during a clear and sunny autumn day - Milosevic, Dragan; Dunjić, Jelena; Stojanović, Vladimir (Geographica Pannonica, 2020)
Saline habitats of the Pannonian plain are very specific regarding their extraordinary biodiversity with many endemic species, but they are among the most threatened European communities, with very limited spatial distribution. Such habitats exist in the Autonomous Province of Vojvodina in the north of Serbia, in the area of Srednja Mostonga, and they are currently in the procedure of protection as the II category protected area - “region of exceptional characteristics”. Great variety of rare and endemic species makes this area interesting for recreational and educational activities. In this paper we investigate micrometeorological and outdoor thermal comfort conditions in different natural environments at the area of Srednja Mostonga. This is the first micrometeorological field measurement study conducted in this region. Measurements were performed during the daytime of a sunny autumn day in 2019. The results showed that air temperature was up to 3.4 °C lower in forest compared to steppe, while relative humidity was up to 5-6% higher in forest than in steppe with up to 3.2 m/s lower wind speeds in forest than in steppe area. Micrometeorological values were similar between forest-steppe and steppe. However, the outdoor thermal comfort conditions expressed via Humidex index showed that ‘some discomfort’ was most often observed in forest-steppe during 27% of measurement time, followed with 13% of ‘some discomfort’ observed in steppe and only 1% of ‘some discomfort’ was observed in forest. Accordingly, during the warmest daytime hours outdoor activities could be performed in forest, while early morning and evening hours could be spent in steppe and forest-steppe areas of Donja Mostonga.